IDENTIFICATION OF IMAGE AREA CONCEPT OF TSUNAMI DISASTER RESPONSE IN COASTAL SPATIAL Case Study : Serangan Island, Denpasar, Bali - Darmawan, I Gede Surya (Journal of Architectural Research and Education, 2020)
Serangan Island is one of the favourite tourist destinations in Bali which is the result of reclamation in 1995-1998, famous for its image as "Turtle Island", the presence of Sakenan Temple, white sand beaches, marine tourism, watersport, coral reef cultivation and seaweed, and the the fishing village of Bugis and Bali. However, behind the many tourism potentials, Serangan Island is threatened with earthquakes and tsunamis because the island is located on the south coast facing the Indian Ocean and the island's relatively low topography and inland elevation. In 2014, the Provincial Government of Bali through the Regional Disaster Management Agency (BPBD) built a communal space in the form of a Temporary Evacuation Place (TES) which is integrated with the Serangan Village Market. This research will identify in detail the implementation of the concept of the image of the disaster response area in the coastal area of Serangan Island. The research method used is descriptive qualitative with purposive sampling, with the use of the image theory of the area and disaster response architecture as the basis of this research. The results of the study show that the concept of the image of the Serangan Island area has also applied the concept of disaster mitigation both in architecture and in spatial planning. This identification has been seen in the concept of paths, edges, districts, nodes and landmarks. The main attacks are on residential areas, although in some parts the potential and function of disaster mitigation aspects need to be maximized.Keywords – image area concept, tsunami disaster response, coastal spatial